Mine Action in Afghanistan - Maley, William (Refuge: Canada’s Journal on Refugees, 1998)
Afghanistan is severely contaminated by anti-personnel mines, which pose major physical, social and economic threats to repatriating refugees. Fortunately, mine action - a multidimensional effort to address these problems through survey, detection, clearance, mine awareness, and victim assistance - is well developed in Afghanistan, with the Afghan Mine Action Program a model of good practice. That said, mine action faces ongoing challenges, of which those originating in the realm of politics are the most troubling.